2013
DOI: 10.1093/cid/cit245
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Serum Fibrosis Markers for Screening and Staging Chronic Hepatitis C Virus Patients in a Large US Cohort

Abstract: In a large observational cohort, FIB-4 was good at differentiating 5 stages of chronic HCV infection. It can be useful in screening patients who need biopsy and therapy, for monitoring patients with less advanced disease, and for longitudinal studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
102
3
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(118 citation statements)
references
References 32 publications
10
102
3
3
Order By: Relevance
“…The mean AUROC values were found to be 0.71−0.83; sensitivity, specificity, PPV, and NPV were found to be 62%−74%, 60%−77%, 37%−83%, and 76%−94.7%, respectively, according to various cut-offs in the studies performed with FIB-4 (10,22,(24)(25)(26)28,30,31). In our study, according to the Ishak and Knodell classifications, the mean AUROC values in the diagnosis of significant/severe fibrosis were −0.72 and -0.67, respectively, and sensitivity, specificity, PPV, and NPV were found to be 67%−70%, 61%−68%, 17%−30%, and 88-96%, respectively.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The mean AUROC values were found to be 0.71−0.83; sensitivity, specificity, PPV, and NPV were found to be 62%−74%, 60%−77%, 37%−83%, and 76%−94.7%, respectively, according to various cut-offs in the studies performed with FIB-4 (10,22,(24)(25)(26)28,30,31). In our study, according to the Ishak and Knodell classifications, the mean AUROC values in the diagnosis of significant/severe fibrosis were −0.72 and -0.67, respectively, and sensitivity, specificity, PPV, and NPV were found to be 67%−70%, 61%−68%, 17%−30%, and 88-96%, respectively.…”
Section: Discussionmentioning
confidence: 93%
“…NPV and PPV have been found to be 86%-88% for the detection of significant fibrosis and cirrhosis (9). However, in later studies, a wide range of sensitivity, specificity, PPV, NPV, and AUROCs values were found: 71%-97%, 13%-74%, 34%-84%, 43%-92%, and 0.6%-0.86, respectively (9,10,(22)(23)(24)(25)(26)(27)(28)(29). The occurrence of different results may be associated with the number of patients with significant fibrosis and AST.…”
Section: Discussionmentioning
confidence: 98%
“…1,4,7,8 Unfortunately, at the time of our study, transient elastography was unavailable at our center. While some investigators have focused on a combination of laboratory tests such as reversal of AST/ALT ratio or APRI, others have been searching for novel markers of fibrosis and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…5 The attempts to find reliable non-invasive markers of liver fibrosis have recently increased dramatically as a result of the evolving novel therapies for hepatitis C and B. 6,7 By analogy, a considerable interest has arisen in extending this work into the field of non-alcoholic fatty liver disease (NAFLD) because of its increased prevalence. 8,9 Moreover, recent long term studies suggest that development of fibrosis in NAFLD has an important prognostic significance.…”
Section: Introductionmentioning
confidence: 99%
“…Bu testlerin büyük bir kısmı fibrozun varlığını ya da yokluğunu göstermekte, ancak derecelendirmesini yapamamakla birlikte son yıllarda kullanılan aspartat aminotransferaz (AST)/trombosit oranı indeksi, AST/ALT oranı gibi testlerle fibroz evrelemesi de kısmen yapılabilmektedir. İleri fibrozu olan hastalar da siroz açısından klinik (splenomegali, karında asit, palmer eritem, periferik telanjiyektaziler) ve laboratuvar (serum bilirübin ve albümin düzeyleri, protrombin zamanı) bulgularıyla değerlendirilmelidir (85)(86)(87).…”
Section: Karaciğer Hastalığının şIddeti Ve Bazal Virolojik Göstergelerunclassified